Inisiasi Program Kegiatan Ekstrakurikuler English Club di SMP 14 Jember - Titik Ismailia; Adriadi Novawan; Nanik Mariyati; Meiga Rahmanita; Ikhwan Huda Al Mujib (Universitas 45 Surabaya, 2025)
The English Club in one of the extracurricular activities organized by schools from elementary to tertiary level. This activity aims to provide a platform for students to develop their interests and talents, especially in the field of English. SMP 14 Jember is one of the schools located in Antirogo village, Sumbersari Jember district which does not yet have an extracurricular activity program in the field of English or English Club. This happened because there were enough personnel who could help carry out this activity. However, teachers and students have tried to hold activities that are competitions in English when there were students who did internship program at the school. The solution offered is to help initiate and assist the development of English Club extracurricular activities such as story telling, speeches and debating. Implementation methods include: conducting preliminary studies, implementing activities, and evaluating. The targets and outputs that have been achieved include 3 mandatory outputs and one additional output, namely: a scientific article published in the Community Service journal, an article in print/electronic mass media, a video of activities, and increasing partner empowerment, namely the formation of the English Club extracurricular activity at SMP 14 Jember.